Design and Evaluation of a Temperature–Humidity Control System for Mushroom Cultivation Using a DHT11 Sensor - Suryaman Suryaman; Siti Hadiaty Yuningsih; Aan Eko Setiawan; Kiki Zakaria (CV. Generasi Intelektual Digital, 2025)
Oyster mushroom (Pleurotus ostreatus) cultivation requires stable temperature and humidity conditions to support optimal mycelial development and fruiting body formation. This study aims to develop and evaluate a low-cost temperature–humidity monitoring and control system for an oyster mushroom cultivation room using a DHT11 sensor integrated with an Arduino-based controller. An experimental evaluation was conducted by comparing DHT11 temperature and humidity readings with a reference measuring instrument under cultivation-room conditions, while the control function was tested using threshold-based rules for activating environmental actuators (heater, fan, and humidifier). The results indicate that the DHT11 sensor produced measurements close to the reference instrument within the tested range, with temperature differences of 0.1–0.3°C and humidity differences of 0.2–0.4%RH across the observations. These findings suggest that the proposed system is feasible for basic environmental monitoring and supports automated threshold-based control for maintaining cultivation conditions near recommended ranges. Sensor performance and measurement stability are influenced by practical factors such as airflow, proximity to heat or moisture sources, and sensor placement; therefore, appropriate placement and shielding are important to minimize local bias. The originality of this work lies in providing an implementable prototype and an empirical sensor performance assessment in a mushroom cultivation environment, offering practical guidance for low-cost smart farming applications.